The Current Situation of Court Testimony of Witnesses in Civil Online Litigation and the Improvement of its Paths - Zheng, Shuwen (International Journal of Social Sciences and Public Administration, 2025)
With the development of online litigation, the appearance of witnesses in court as an important part of litigation is also facing a transformation towards the online way of testifying in court. The emergence of online court testimony has revolutionized the relevant meanings in traditional civil litigation and possesses the institutional advantages of economy and convenience that offline testimony does not have. However, problems such as the unclear mechanism for initiating the system, the difficulty in verifying the identity of witnesses, and the lack of guarantee for the principle that witnesses are not allowed to attend as observers have also restricted the application of the online testimony system. In the future, the procedural choice rights of witnesses should be clearly defined in the form of law, the review procedures for witness identities should be standardized, and a standardized testimony environment should be provided for witnesses to testify, so as to ensure the effective operation of the online witness testimony system.